Perspectives on optimizing local delivery of drugs to peripheral nerves using mathematical models. Issue 2 (9th January 2023) - Laranjeira, Simao; Roberton, Victoria H.; Phillips, James B.; Shipley, Rebecca J.
Abstract: Drug therapies for treating peripheral nerve injury repair have shown significant promise in preclinical studies. Despite this, drug treatments are not used routinely clinically to treat patients with peripheral nerve injuries. Drugs delivered systemically are often associated with adverse effects to other tissues and organs; it remains challenging to predict the effective concentration needed at an injured nerve and the appropriate delivery strategy. Local drug delivery approaches are being developed to mitigate this, for example via injections or biomaterial‐mediated release. We propose the integration of mathematical modeling into the development of local drug delivery protocols for peripheral nerve injury repair. Mathematical models have the potential to inform understanding of the different transport mechanisms at play, as well as quantitative predictions around the efficacy of individual local delivery protocols. We discuss existing approaches in the literature, including drawing from other research fields, and present a process for taking forward an integrated mathematical‐experimental approach to accelerate local drug delivery approaches for peripheral nerve injury repair. This article is categorized under: Neurological Diseases > Molecular and Cellular Physiology Neurological Diseases > Computational Models Neurological Diseases > Biomedical Engineering Abstract : Numerous local drug delivery approaches are being developed to treat peripheral nerve injuries and to avoid adverse effects induced by systemic delivery. Exploring and optimizing the numerous delivery strategies using an experimental approach in isolation has proven to be a barrier to innovation. Here, a novel framework is proposed, where in silico and experimental models are devised in parallel.